Potential causes and significance of elevated blood ketone levels in patients with heart failure with preserved ejection fraction - Lu, Weijie; Liu, Ai; Liu, Mengyang; Hu, Yujie; Yang, Kang; Deng, Yaoting; Li, Qianrong; Wang, Bowen; Li, Yanling; Jiang, Bing; Wang, Gang; Wang, Xuehan; et al. (Frontiers in Nutrition, 2026)
BackgroundThe diagnosis of heart failure with preserved ejection fraction (HFpEF) remains challenging. Given the critical role of metabolic disturbance and energy expenditure in HFpEF pathophysiology, we investigated the clinical significance and diagnostic value of blood ketone bodies in these patients.MethodsThis case–control study enrolled 160 participants, comprising 80 HFpEF patients and 80 matched healthy controls. Baseline characteristics, levels of blood ketones (acetoacetate, β-hydroxybutyrate, acetone), and NT-proBNP were compared. Multivariate linear regression and correlation analyses were employed to assess the associations between ketone levels, clinical parameters, and NT-proBNP. The diagnostic performance was evaluated using receiver operating characteristic (ROC) curve analysis.ResultsCompared to controls, HFpEF patients showed significant differences in age, heart rate, BMI, and blood pressure. Multivariate regression revealed a significant linear association between BMI, systolic blood pressure, and acetoacetate levels in the HFpEF group. A weak inverse correlation was found between acetoacetate and NT-proBNP levels. However, no correlation was observed between ketone levels and NYHA functional class. ROC analysis demonstrated that the combination of acetoacetate and NT-proBNP yielded the highest diagnostic efficacy (AUC = 0.9117), superior to NT-proBNP alone (AUC = 0.8328) or any ketone body alone.ConclusionUnlike nutritional ketosis, elevated blood ketone levels in patients with HFpEF likely reflect impaired metabolic efficiency rather than a marker of cardiac function. Nevertheless, this phenomenon has diagnostic significance: combining acetoacetate with NT-proBNP can markedly improve diagnostic performance.